A balanced introduction to computer science - Reed, David (Pearson, 2011)
This text uses the Internet as a central theme, studying its history, technology, and current use. Experimental problems use Web-based tools, enabling students to learn programming fundamentals by developing their own interactive Web pages with HTML and JavaScript.